Jisuikang Promotes the Repair of Spinal Cord Injury in Rats by Regulating NgR/RhoA/ROCK Signal Pathway. (28th November 2020) - Wu, Chengjie; Zhou, Yuxin; Tu, Pengcheng; Yang, Guanglu; Zheng, Suyang; Pan, Yalan; Sun, Jie; Guo, Yang; Ma, Yong
Abstract : Jisuikang (JSK) is an herbal formula composed of many kinds of traditional Chinese medicine, which has been proved to be effective in promoting the rehabilitation of patients with spinal cord injury (SCI) after more than ten years of clinical application. However, the mechanisms of JSK promoting nerve regeneration are yet to be clarified. The aim of this study was to investigate the effects of JSK protecting neurons, specifically the regulation of NgR/RhoA/ROCK signal pathway. The motor function of rats was evaluated by the BBB score and inclined plate test, Golgi staining and transmission electron microscope were used to observe the microstructure of nerve tissue, and fluorescence double-labeling method was used to detect neuronal apoptosis. In this study, we found that JSK could improve the motor function of rats with SCI, protect the microstructure (mitochondria, endoplasmic reticulum, and dendritic spine) of neurons, and reduce the apoptosis rate of neurons in rats with SCI. In addition, JSK could inhibit the expression of Nogo receptor (NgR) in neurons and the NgR/RhoA/ROCK signal pathway in rats with SCI. These results indicated JSK could improve the motor function of rats with SCI by inhibiting the NgR/RhoA/ROCK signal pathway, which suggests the potential applicability of JSK as a nerve regeneration agent.